Variations in the protein level of Omi/HtrA2 in the heart of aged rats may contribute to the increased susceptibility of cardiomyocytes to ischemia/reperfusion injury and cell death: Omi/HtrA2 and aged heart injury - Wang, Ke (Springer Netherlands, 2012)
Survival after acute myocardial infarction is decreased in elderly patients. The enhanced rates of apoptosis in the aging heart exacerbate myocardial ischemia/reperfusion (MI/R) injury. We have recently demonstrated that the X-linked inhibitor of apoptosis protein (XIAP), the most potent endogenous inhibitor of apoptosis, was decreased in aging rats’ hearts. XIAP was balanced by two mitochondria proteins, Omi/HtrA2 and Smac/DIABLO. However, the implicative role of XIAP, Omi/HtrA2, and Smac/DIABLO to aging-related MI/R injury has not been previously investigated. In our study, male aging rats (20–24 months) or young adult rats (4–6 months) were subjected to 30 min of myocardial ischemia followed by reperfusion. MI/R-induced cardiac injury was enhanced in aging rats, as evidenced by aggravated cardiac dysfunction, enlarged infarct size, and increased myocardial apoptosis (TUNEL and caspase-3 activity). Then, the XIAP, Omi/HtrA2, and Smac/DIABLO protein and mRNA expression was detected. XIAP protein and mRNA expression was decreased in both aging hearts and aging hearts subjected to MI/R. Meanwhile, myocardial XIAP protein expression was correlated to cardiac function after MI/R. However, Omi/HtrA2, but not Smac/DIABLO, expression was increased in aging hearts. Moreover, the translocation of Omi/HtrA2 from mitochondria to cytosol was increased in both aging hearts and aging hearts subjected to MI/R. Treatment with ucf-101 (a novel and specific Omi/HtrA2 inhibitor) attenuated XIAP degradation and caspase-3 activity and exerted cardioprotective effects. Taken together, these results demonstrated that increased expression and leakage of Omi/HtrA2 enhanced MI/R injury in aging hearts via degrading XIAP and promoting myocardial apoptosis.